1959
DOI: 10.1139/y59-011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Renal Response to Plasma Volume Expansion

Abstract: Expansion of the plasma volume by infusions either of plasma or iso-oncotic albumin solution resulted almost uniformly in diuresis and natriuresis in anaesthetized dogs. Although the clearance of para-aminohippurate (RPF) usually increased, changes in clearance of creatinine (GFR) were neither large nor consistent in direction, indicating that the renal response depended on altered tubular reabsorption. The usual temporal dissociation between the peak values for water and sodium output during the response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1961
1961
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Gilmore and Weisfeldt (1965) found that either bilateral vagotomy or carotid sinus denervation attenuated the diuretic but not the natriuretic response to acute intravascular volume expansion, whereas Pearce (1959) concluded that neither vagal nor carotid sinus pathways are necessary to elicit a natriuretic or diuretic response to the same stimulus. Atkins and Pearce (1959) later found that bilateral vagotomy significantly attenuated both the diuretic and natriuretic responses to acute intravascular volume expansion if the animals had not previously been hydrated. Although Pearce (1968) found that the chronic spinal dog (C 8 ) showed no diuresis or natriuresis in response to acute volume expansion, Michaelis and Gilmore (1969) still observed diuretic and natriuretic responses to volume expansion in the acute spinal animal (Cs), as did McDonald et al (1970) …”
Section: Discussionmentioning
confidence: 98%
“…Gilmore and Weisfeldt (1965) found that either bilateral vagotomy or carotid sinus denervation attenuated the diuretic but not the natriuretic response to acute intravascular volume expansion, whereas Pearce (1959) concluded that neither vagal nor carotid sinus pathways are necessary to elicit a natriuretic or diuretic response to the same stimulus. Atkins and Pearce (1959) later found that bilateral vagotomy significantly attenuated both the diuretic and natriuretic responses to acute intravascular volume expansion if the animals had not previously been hydrated. Although Pearce (1968) found that the chronic spinal dog (C 8 ) showed no diuresis or natriuresis in response to acute volume expansion, Michaelis and Gilmore (1969) still observed diuretic and natriuretic responses to volume expansion in the acute spinal animal (Cs), as did McDonald et al (1970) …”
Section: Discussionmentioning
confidence: 98%
“…With regard to the role of cardiac receptors in mediating the renal responses to outright volume expansion, it has been shown that cervical vagotomy, which interrupts vagally innervated cardiopulmonary receptor input to the central nervous system, attenuates the diuretic response to volume expansion in the dog (Atkins and Pearce, 1959;Gilmore and Weisfeldt, 1965), but fails to do so in the monkey (Gilmore et al, 1979). In addition, thoracic sympathectomy, which removes spinal sensory input from the cardiopulmonary region (Malliani, 1979), has no effect on the renal responses of the monkey to volume expansion (Cornish and Gilmore, 1983).…”
Section: Renal Responses Of the Cardiac-denervated Nonhuman Primate Tmentioning
confidence: 99%
“…If, as is believed by many, expansion of the total extracellular fluid volume can cause diuresis, then the graded expansion of this compartment induced by saline infusion would be more likely to cause a diuresis. Atkins & Pearce (1959), among others, have shown that infusion of 200 ml. of plasma causes a rise in urinary flow in normal dogs.…”
Section: Resultsmentioning
confidence: 94%